2021
DOI: 10.1111/ejn.15430
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in odour detection and hedonic ratings of unpleasant smells in asymptomatic university students as SARS‐Cov‐2 emerged locally

Abstract: Sudden olfactory loss in the absence of concurrent nasal congestion is now a well‐recognized symptom of COVID‐19. We examined olfaction using standardized objective tests of odour detection, identification and hedonics collected from asymptomatic university students before and as SARS‐CoV‐2 emerged locally. Olfactory performance of students who were tested when the virus is known to be endemic (n = 22) was compared to students tested in the month prior to viral circulation (n = 25), a normative sample assessed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Yet, several studies showed a great flexibility of odor hedonic perception. Thus, differences were observed in relation to individual characteristics such as age 10 12 , sex 13 18 , the experience towards odorants 19 and physiological state 20 , 21 , diseases such as depressive disorders 22 , schizophrenia 23 , 24 or Parkinson’s disease 25 , 26 and recently with SARS-CoV-2 27 . Odor hedonic perception also appeared to depend on repeated exposures 28 , 29 , verbal influence 30 , 31 , or stimulus presentation pathway (orthonasal vs. retronasal) 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Yet, several studies showed a great flexibility of odor hedonic perception. Thus, differences were observed in relation to individual characteristics such as age 10 12 , sex 13 18 , the experience towards odorants 19 and physiological state 20 , 21 , diseases such as depressive disorders 22 , schizophrenia 23 , 24 or Parkinson’s disease 25 , 26 and recently with SARS-CoV-2 27 . Odor hedonic perception also appeared to depend on repeated exposures 28 , 29 , verbal influence 30 , 31 , or stimulus presentation pathway (orthonasal vs. retronasal) 32 .…”
Section: Introductionmentioning
confidence: 99%